The Role of Social Media in Shaping English Language Learning Practices among Uzbek School Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the transformative influence of social media platforms on English language learning practices among school students in Uzbekistan. In an age of rapid technological advancement and global connectivity, social media has become not just a tool for communication but also a dynamic educational resource. The paper examines how platforms such as YouTube, Instagram, Telegram, TikTok, and Facebook are being used by Uzbek students as informal learning environments to improve their English language skills, including vocabulary acquisition, pronunciation, listening comprehension, and conversational fluency. Drawing on data collected through surveys, interviews, and classroom observations involving students and English teachers from various schools across Uzbekistan, the study reveals a growing trend of digital engagement outside the traditional classroom. It shows that students are increasingly motivated to learn English due to the interactive and authentic language exposure provided by social media content such as vlogs, language learning channels, memes, short videos, and online communities. Furthermore, the research highlights the role of peer-to-peer communication on these platforms, which creates a collaborative and immersive learning experience. The study also addresses the challenges and limitations of relying on social media for language learning. These include the potential for exposure to incorrect or non-standard language forms, distractions from unrelated content, lack of academic structure, and digital literacy gaps. Teachers’ perspectives underscore the importance of integrating social media into formal learning in a balanced and pedagogically sound manner, leveraging its benefits while mitigating its risks. The article emphasizes that social media—when used purposefully and under appropriate guidance—can serve as a powerful supplementary tool in English language education. It promotes learner autonomy, increases exposure to authentic language use, and fosters a more engaging and motivating environment for students. The findings have practical implications for educators, policymakers, and curriculum developers seeking to modernize English language teaching methods in Uzbekistan by embracing the digital habits of today’s learners.